4R nitrogen fertilizer management in cotton production. Issue 3 (9th May 2019) - Flis, Sally
Abstract : Nitrogen supply for cotton is critical for vegetative growth, development of fruiting sites, and yield. Considerations for the 4Rs in nitrogen management in cotton are quite different from those for corn due to differences in the growth and nitrogen uptake patterns of the plant and the soils and climates in which cotton is commonly grown. Earn 0.5 CEUs in Nutrient Management by reading this article and taking the quiz at www.certifiedcropadviser.org/education/classroom/classes/684 .